Implementasi Kurikulum PAI: Kurikulum Ideal, Aktual dan Kurikulum Tersembunyi di SMKs 6 Pertiwi Curup - rasmini rasmini; Deriwanto Deriwanto (Yayasan Literasi Kita Indonesia, 2022)
Research Objectives To find out the Implementation of Islamic Education Curriculum: Ideal Curriculum, Actual and Hidden Curriculum (Hidden Curiculum) in Schools. SMKs 6 PERTIWI CUUP Field research (Field Research) conducted by the author, using a descriptive qualitative research method that describes and clearly describes things that happen in the field. The ideal curriculum is clearly visible in its form, such as the Learning Objectives Module and Flow (ATP), the implementation of the PAI curriculum is intended to make the curriculum an important part of the development of students. The actual curriculum is a curriculum that is made in accordance with events in the field, the hidden curriculum plays an important role in instilling the values of patriotism, honesty, courtesy and politeness to students. This curriculum is guided by the PANCASILA profile. 1. have faith and fear God Almighty and have good character, 2. critical reasoning, 3 independent, 4. gotong royong, global diversity and 6. creative. because the students themselves are makers of actions, so that children will remember and understand what they have learned better.